ANALISIS FAKTOR-FAKTOR PENDORONG PERUBAHAN POLA SPASIAL TERHADAP DRAINASE PERKOTAAN DI KECAMATAN DENPASAR BARAT - ANAK AGUNG RATU RITAKA WANGSA; TJOKORDA ISTRI PRAGANINGRUM; IDA BAGUS SURYATMAJA; NI LUH MADE AYU MIRAYANI PRADNYADARI (Universitas Mahasaraswati K. Mataram, 2024)
Changes in spatial patterns, especially the transformation of land from green open spaces to built-up areas, have caused various impacts on the environment and urban drainage systems. This study analyzes the driving factors of spatial pattern change on urban drainage in West Denpasar District, with a special focus on Padangsambian Kelod Village and Pemecutan Kelod Village. This study aims to identify and understand the factors that contribute to changes in the drainage system in the region. The research methods used include collecting spatial data through satellite imagery and thematic maps, field surveys for direct observation, and interviews with residents and related stakeholders. The collected data was then analyzed qualitatively and quantitatively to identify spatial change patterns and their driving factors. The results show that the change in spatial patterns towards urban drainage in West Denpasar District is driven by several main factors, including rapid population growth, intensive infrastructure development, and land use change from agricultural to residential and commercial. These factors have led to increased surface runoff, decreased drainage capacity, and increased flood risk in the region. This study concludes that a more integrated and sustainable drainage management approach is needed to overcome the challenges posed by changes in spatial patterns. The recommendations submitted include increasing drainage capacity, implementing environmentally friendly development practices, and increasing public awareness about the importance of maintaining urban drainage systems.